2005
DOI: 10.1074/jbc.m411155200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of a 92-Residue C-terminal Fragment of TonB from Escherichia coli Reveals Significant Conformational Changes Compared to Structures of Smaller TonB Fragments

Abstract: Uptake of siderophores and vitamin B 12 through the outer membrane of Escherichia coli is effected by an active transport system consisting of several outer membrane receptors and a protein complex of the inner membrane. The link between these is TonB, a protein associated with the cytoplasmic membrane, which forms a large periplasmic domain capable of interacting with several outer membrane receptors, e.g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 48 publications
(65 reference statements)
5
47
2
Order By: Relevance
“…Interaction studies of FhuA with TonB showed an intermediate 1:1 complex and a stable 1:2 complex, the latter of which increased upon the addition of ferricrocin as an FhuA ligand (164). These findings are supported by the crystal structure of the C-terminal domain of TonB, revealing dimer formation, which, however, seems to depend on the length of the recombinant protein fragments chosen (169). A crystal structure of FhuA in complex with the TonB C-terminal domain was solved recently (245), which showed the interaction between the receptor and the energy transducer in more detail (Fig.…”
Section: General Steps Of Siderophore Pathwayssupporting
confidence: 71%
“…Interaction studies of FhuA with TonB showed an intermediate 1:1 complex and a stable 1:2 complex, the latter of which increased upon the addition of ferricrocin as an FhuA ligand (164). These findings are supported by the crystal structure of the C-terminal domain of TonB, revealing dimer formation, which, however, seems to depend on the length of the recombinant protein fragments chosen (169). A crystal structure of FhuA in complex with the TonB C-terminal domain was solved recently (245), which showed the interaction between the receptor and the energy transducer in more detail (Fig.…”
Section: General Steps Of Siderophore Pathwayssupporting
confidence: 71%
“…15,16 It was also in accord with the observation of conformational transitions in the structure of some receptors on the periplasmic side after binding of cargo molecules. 17,18 Crystal and NMR structures of the C-terminal globular domain of TonB alone 15,19 and in complex with outer membrane receptors 20,21 have been reported. In the complexes the domain was in contact with the socalled TonB-box of the receptors, a conserved stretch of $7 amino acids near the periplasmic N-terminal end of the cork domain.…”
Section: Introductionsupporting
confidence: 62%
“…3) to cluster at three discrete TonB regions as follows: an N-terminal domain (region I), an intermediate domain (region II), and the C-terminal domain (region III). Three-dimensional structural information has been reported (4,5,30) only for the C-terminal domain of TonB. We mapped (Fig.…”
Section: Methodsmentioning
confidence: 99%